A practical guide for operational validation of discrete simulation models - Leal, Fabiano; da Silva Costa, Rafael Florêncio; Montevechi, Jośe Arnaldo Barra; de Almeida, Dagoberto Alves; Marins, Fernando Augusto Silva [UNESP] (FapUNIFESP (SciELO), 2011)
As the number of simulation experiments increases, the necessity for validation and verification of these models demands special attention on the part of the simulation practitioners. By analyzing the current scientific literature, it is observed that the operational validation description presented in many papers does not agree on the importance designated to this process and about its applied techniques, subjective or objective. With the expectation of orienting professionals, researchers and students in simulation, this article aims to elaborate a practical guide through the compilation of statistical techniques in the operational validation of discrete simulation models. Finally, the guide's applicability was evaluated by using two study objects, which represent two manufacturing cells, one from the automobile industry and the other from a Brazilian tech company. For each application, the guide identified distinct steps, due to the different aspects that characterize the analyzed distributions. © 2011 Brazilian Operations Research Society.
Keywords: Discrete event simulation; Operational validation; Practical guide